2014
DOI: 10.1111/cars.12040
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Schemas for Racial Identity in Canadian Television Advertising

Abstract: What meanings are attached to race in advertising? We analyze a sample of prime-time Canadian television advertising to identify cultural schemas for what it means to be White, Black, and East/Southeast Asian. Our empirical focus is on food and dining advertising. Through quantitative content analysis of associations between race and food subtypes, we show that there are systematic differences in the types of foods that groups are associated with. Through a qualitative content analysis of the commercials, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A 2014 study exploring diversity in advertising by the University of Toronto found that 87% of actors were white, with commercials reproducing “narrow culture schemas” that reinforced dominant associations between color, socio-economic class, and education (Baumann & Ho, 2014, p. 164). The absence of racial diversity in the menstrual suppression advertisements reflects Baumann and Ho's “white natural” and “white highbrow” cultural schemas (pp.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 study exploring diversity in advertising by the University of Toronto found that 87% of actors were white, with commercials reproducing “narrow culture schemas” that reinforced dominant associations between color, socio-economic class, and education (Baumann & Ho, 2014, p. 164). The absence of racial diversity in the menstrual suppression advertisements reflects Baumann and Ho's “white natural” and “white highbrow” cultural schemas (pp.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, individuals develop schemata based on their experiences with supra-individual structures in the form of institutions and then use these schemata to filter new experiences that they have. Examples of such schematic translations are gender schemata that delimit the ways we see individuals as males and females (Stansbury et al, 2003), race schemata which consist of various stereotypes and understandings of given phenotypes (Baumann and Ho, 2014) and countless other schemata made accessible to individuals through media messages and other institutional arrangements (see Altikriti and Al-Mahadin, 2015; DiMaggio, 1997).…”
Section: Schema and The Study Of Culture: From Situated Action To Typmentioning
confidence: 99%
“…Because of many researchers’ tendencies to use the concept of schema as a kind of connective tissue between society and the individual (e.g. Baumann and Ho, 2014; Lamont et al, 2014; Massey, 2014; Vaisey, 2009), however, studies seldom discuss the ways in which these schemata clash, breakdown or entirely fail for individuals. Schemata are typically seen as perceptual filters that cause individuals to see, think and talk about a phenomenon in a certain way, making questions of schematic failure or contradiction both secondary to the emphasis on causation and potentially disruptive due to the fact that they foreground active, often seemingly spontaneous decision-making instead of automatic, patterned response (see Wagoner, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Baumann and Ho ( 2014) conducted a qualitative analysis of cultural schemas for racial representation present in Canadian television commercials. To construct a diverse sample, the researchers recorded commercials featured on three Canadian television networks over 21 evenings during an 18-month period (Baumann & Ho, 2014). To limit their sample size, Baumann and Ho only coded commercials that featured characters in situations related to food and dining.…”
Section: Content Analyses Of Commercialsmentioning
confidence: 99%